Rational Actor Analysis in the Economic Development Conflict of PT Semen Gresik Indonesia in Rembang Regency - Saputri, Omega Karunia Illah Giant; Sudarmo, Sudarmo; Haryanti, Rina Herlina (Universitas Muhammadiyah Malang, 2026)
The conflict between conservation and exploitation of Natural Resources in karst areas is a recurring issue in Indonesia, especially in limestone mining for the cement industry. This study aims to analyze the dynamics of conflict development of PT Semen Gresik cement plant in Rembang Regency using the perspective of rational choice theory. This theory states that state actors, companies, local communities and non-governmental organizations (NGOs) make decisions based on rational calculations of interests, resources and opportunities to maximize profits or minimize losses. This study uses a qualitative method with a systematic literature review approach, this study identifies that the emergence of conflicts in the picu with structural factors such as inequality of participation and manage resources, as well as instrumental factors such as low transparency of licensing. This study addresses the collision between the constellation